Validation of differential cross sections by means of 252Cf spectral averaged cross sections. (February 2018) - Schulc, Martin; Košťál, Michal; Simakov, Stanislav; Rypar, Vojtěch; Harutyunyan, Davit; Šimon, Jan; Burianová, Nicola; Novák, Evžen; Jánský, Bohumil; Mareček, Martin; Uhlíř, Jan
Abstract: The results of systematic evaluations of the spectrum-averaged cross section measurements performed in the spontaneous fission 252 Cf neutron field are presented. The Following threshold reactions were investigated: 23 Na(n, 2n) 22 Na, 54 Fe(n, p) 54 Mn, 54 Fe(n, α) 51 Cr, 27 Al(n, p) 27 Mg, 27 Al(n, α) 24 Na, 19 F(n, 2n) 18 F, 90 Zr(n, 2n) 89 Zr and 89 Y(n, 2n) 88 Y. The spectrum-averaged cross sections for 23 Na(n, 2n) 22 Na, 54 Fe(n, α) 51 Cr and 89 Y(n, 2n) 88 Y reactions were measured for the first time. This quantity is compared with calculations carried with the IRDFF-v1.05 library. There is a notable disagreement exceeding uncertainties only for 54 Fe(n, p) 54 Mn and 54 Fe(n, α) 51 Cr reactions. The spectrum-averaged cross sections were inferred from experimentally determined reaction rates. The experimental reaction rates were derived for irradiated samples from the Net Peak Areas measured using the semiconductor high purity germanium spectroscopy. The presented experimental data can be used to validate nuclear data libraries and reactions used in the practical reactor dosimetry and to specify high energy tail of the 252 Cf neutron spectrum. Highlights: Spectral averaged cross sections in the spontaneous fission 252 Cf neutron field. 23 Na(n, 2n) 22 Na, 54 Fe(n, p) 54 Mn, 54 Fe(n, α) 51 Cr, 27 Al(n, p) 27 Mg, 27 Al(n, α) 24 Na, 19 F(n, 2n) 18 F, 90 Zr(n, 2n) 89 Zr and 89 Y(n, 2n) 88 Y reactions are investigated. Spectral averaged cross sections results are compared with IRDFF library.